Levels and trends in contraceptive prevalence, unmet need, and demand for family planning for 29 states and union territories in India: a modelling study using the Family Planning Estimation Tool - Jin Rou New, MA; Niamh Cahill, PhD; John Stover, MA; Yogender Pal Gupta, PhD; Leontine Alkema, DrPhD (Elsevier, 2017)
Summary: Background: Improving access to reproductive health services and commodities is central to development. Efforts to assess progress on this front have been largely focused on national estimates, but such analyses can mask local disparities. We assessed progress in reproductive health services subnationally in India. Methods: We developed a statistical model to generate estimates and projections of levels and trends in family planning indicators for subpopulations. The model builds onto the UN Population Division's Family Planning Estimation Model and uses data from multiple rounds of the Demographic and Health Survey, the District Level Household & Facility Survey, and the Annual Health Survey. We present annual estimates and projections of levels and trends in the prevalence of modern contraceptive use, and unmet need and demand for family planning for 29 states and union territories in India from 1990 to 2030. We also compared projections of demand satisfied with modern methods with the proposed goal of 75%. Findings: There is a large amount of heterogeneity in India, with a difference of up to 55·1 percentage points (95% uncertainty interval 46·4-62·1) in modern contraceptive use in 2015 between subregions. States such as Andhra Pradesh, with 92·7% (90·9-94·2) demand satisfied with modern methods, are performing well above the national average (71·8%, 56·7-83·6), whereas Manipur, with 26·8% (16·7-38·5) of demand satisfied, and Meghalaya, with 45·0% (40·1-50·0), consistently lag behind the rest of the country. Manipur and Meghalaya require the highest percentage increase in modern contraceptive use to achieve 75% demand satisfied with modern methods by 2030. In terms of absolute numbers, Uttar Pradesh requires the greatest increase, needing 9·2 million (5·5-12·6 million) additional users of modern contraception by 2030 to meet the target of 75%. Interpretation: The demand for family planning among the states and union territories in India is highly diverse. Greatest attention is needed in Uttar Pradesh, Manipur, and Meghalaya to meet UN targets. The analysis can be generalised to other countries as well as other subpopulations. Funding: Avenir Health through a grant from the Bill & Melinda Gates Foundation.